Ab initio Study on the IOOCl Isomers and Reaction Pathways of the IO+ClO Reaction - T. K. Ghosh; S. Yabushita (International Journal of Research in Chemistry and Environment (IJRCE), 2018)
Ab initio calculations have been performed to investigate various minimum energy geometries, transition state geometries of the reaction between IO and ClO radicals. Geometries and frequencies have been identified at the MP2 level of theory using SDB(Stuttgart-Dresden-Bonn)TZ basis set for iodine and cc-pVTZ basis sets for chlorine and oxygen along with (s,p) diffuse functions for all the three atoms. The energetics have been studied at the QCISD(T) level of theory. Most of the data are reported to be new in literature. Possible reaction pathways for the different product formations have been discussed on the basis of geometries and energetics along with the results of IRC calculations.